Recent advances in understanding Leishmania donovani infection: The importance of diverse host regulatory pathways. Issue 7 (23rd April 2018) - Saha, Amrita; Basu, Moumita; Ukil, Anindita
Abstract: Invasion of host cell by pathogens induce various intracellular signalling pathways. The host cell through the initiation of these signalling circuits desperately wants to get rid of the pathogen, whereas the pathogen tries to subvert these defence strategies to create an environment for their successful survival. Leishmania spp . is not an exception. Leishmania have to evolve a range of strategic mechanisms to neutralize macrophage defensive arsenals which enable the parasite to replicate within the phagolysosome of infected host. Understanding these signalling mechanisms in detail will not only improve our basic knowledge of host‐pathogen interaction but will also help us to develop effective drug targets not only against leishmaniasis but also for many other macrophage associated diseases. © 2018 IUBMB Life, 70(7):593–601, 2018